A straightforward catalytic approach to obtain deuterated chloroform at room temperature. (6th July 2020) - Higuera‐Padilla, Angel Ruben; Kock, Flávio Vinícius Crizóstomo; Batista, Alzir Azevedo; Colnago, Luiz Alberto
Abstract: We report the catalytic activity for the complexes— cis ‐[RuCl2 (dppb)(bipy)] (A ), and [η 6 ‐( p ‐cymene)Ru (dppb)Cl]PF6 (B ), wherein dppb = 1, 4‐bis(diphenylphosphine)butane, and bipy = 2, 2′‐bipyridine—for the synthesis of CDCl3 from CHCl3 using D2 O as deuterium source. H/D exchange reactions were performed using a chloroform/D2 O, 1:2 molar ratio, vigorously stirred, at room temperature. One mole of KOH was dissolved in D2 O fraction and catalytic complexes from 0.002 to 0.05 mmol were dissolved in chloroform. The H/D exchange reactions were monitored using 13 C nuclear magnetic resonance sequences without proton decoupling. The reaction using 0.01 mmol of compound A reached approximately 55% of H/D conversion in 1 h. In the same time, the reactions with 0.002 mmol of compound A and without catalyst show approximately 28% and 3% H/D exchange, respectively. Without the catalysts, the H/D exchange was only 12.0% in 5 h. For compound B, 55% H/D conversion was observed in 1 h, only when 0.05 mmol was used, which is much higher catalyst concentration. After the isolation of the chloroform fraction and two more addition of D2 O, it was possible to obtain 95.0% H/D exchange in approximately 3 h, using 0.01 mmol of the compound A. Therefore, compound A is an efficient catalyst for a rapid and straightforward synthesis of CDCl3 from CHCl3 at room temperature and using D2 O as deuterium source.